If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -12 = 5x + 2 Reorder the terms: -12 + 7x = 5x + 2 Reorder the terms: -12 + 7x = 2 + 5x Solving -12 + 7x = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 7x + -5x = 2 + 5x + -5x Combine like terms: 7x + -5x = 2x -12 + 2x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + 2x = 2 + 0 -12 + 2x = 2 Add '12' to each side of the equation. -12 + 12 + 2x = 2 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 2 + 12 2x = 2 + 12 Combine like terms: 2 + 12 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 7(a-6)+4=2(a-4) | | 36xr=2 | | 2(x+6)-4x=7 | | -5w+7=-29-w | | 2x-64=5x+8 | | 14x+1=0 | | 2l+2(1/2l)=180 | | 7/9x=-14 | | 4x+8-3x=18 | | 5-3x=-7x+5 | | 8x+3-7x=10 | | 4(x+24)=128 | | 6x+20=100 | | -7x-3(-5x+8)=-88 | | 2(1/2) | | 5x^2+12x-1=0 | | 28-2x=6x | | 8^3/2 | | x+89=10x+8 | | 163-7x=29x+15 | | (x^3)/18 | | 9x+3=187 | | x^2+6x+8=24 | | (n+3)*6=72 | | S=C+x | | a/4+4=8 | | x^2-14x+4=0 | | 6x-12y-24=0 | | 14+14z=-8-6z | | Y=-.75x+4.5 | | 5(3-7a)=-230 | | 4x+9=99-6 |